'Red mist' homicide: sexual infidelity and the English law of murder (glossing Titus Andronicus). (10th October 2012) - Howe, Adrian
<x xml:space="preserve">Abstract</x> For over 300 years, criminal courts have regarded sexual infidelity as sufficiently grave provocation as to provide a warrant, indeed a 'moral warrant', for reducing murder to manslaughter. While the warrant has spilled over into diminished responsibility defences, wounding, grievous bodily harm and attempted murder cases, it is provocation cases that have provided the precedents enshrining a defendant's impassioned homicidal sexual infidelity tale as excusatory. Periodically, judges and law reformers attempt to reign in provocation defences, most recently in England and Wales where provocation has been replaced by a loss of control defence that, most controversially, specifically excludes sexual infidelity as a trigger for loss of control. This paper reflects on this reform and its reception, glossing Shakespeare's scathing critique of warrants for murder in Titus Andronicus.